Analisis Pengelolaan Citra Lembaga Pendidikan: Implikasinya Pada Keputusan Konsumen Dalam Memilih Program Studi Manajemen Pendidikan Islam - Nurbawani, Aris (Universitas Islam Negeri Raden Intan Lampung, 2023)
Many previous studies have analyzed the activities of educational institutions to build and improve the image of their institutions. Considering the importance of the image of educational institutions, there are educational institutions that delegate special tasks to improve the image of this institution to public relations. This interesting research was conducted to examine the influence of the image of educational institutions on consumer behaviour in choosing the Islamic Education Management (MPI) study program at IAIN Ponorogo. As is known, every educational institution's marketing efforts ultimately result in consumer purchasing decisions. Consumer decisions in purchasing can be understood as one of consumer behaviour. This research includes quantitative research. Data were collected using a questionnaire tool using Google Forms for 112 respondents from 165 populations. The research results show that the educational institution image variable has a significant and positive effect on consumer behaviour in choosing a major in the MPI study program at IAIN Ponorogo. The coefficient of determination shows that the consumer behaviour variable in choosing the MPI study program at IAIN Ponorogo is influenced by the image variable of the educational institution by 42,9% while the remaining 57,1% is influenced by other factors outside this research model. Based on the test results, it was found that the linear regression equation Y = 1.001x+18.944, meaning that every 1 unit change in the image of an educational institution will positively influence consumer behaviour in choosing the MPI study program at IAIN Ponorogo by 1.001.